Microbial degradation of n-hexadecane using Pseudomonas aeruginosa PU1 isolated from transformer-oil contaminated soil. (November 2021) - Domdi, Latha; Lakra, Avinash Kant; Mohan, Surapaneni Krishna; Tilwani, Younus Mohd; Jha, Natwar; Arul, Venkatesan
Abstract: The present work is carried out to determine the biodegradation potential of n -hexadecane by bacterial strain P. aeruginosa PU1 isolated from soil polluted with transformer oil. The bacteria showed its ability to grow in n -hexadecane containing medium and its utilization was revealed by a 2, 6-dichlorophenol indophenol assay, where complete decolorization of the medium occurred on the 5 th day, at 35 °C. During the n -hexadecane degradation, maximum alkane hydroxylase (147 μmol min −1 mg −1 ) and alcohol dehydrogenase (113 μmol min −1 mg −1 ) activities were noticed at 3 rd day of incubation. The production of such enzymes is important in the degradation of long-chain alkanes. On 10 days of incubation, P . aeruginosa PU1 degraded 100% n -hexadecane as performed by gravimetric analysis. The formation of P . aeruginosa PU1 biofilm in n -hexadecane containing medium was observed by the Scanning electron microscope (SEM) and intracellular accumulation of n -hexadecane was confirmed by Transmission electron microscope (TEM). Further, studies on ex-situ biodegradation results obtained from the Fourier transform infrared (FT-IR) and Gas Chromatography-Mass Spectrometer (GC-MS) analysis were interrelated with data obtained from Zeta Potential (ZP), Contact Angle (CA) measurement, and Gravimetric Analysis (GA) which showed the hydrophilic nature of the medium due to the production of acids and alcohol on the degradation of n -hexadecane. The biodegradation of the n -hexadecane resulted in the formation of products such as 3-pentyn-1-ol (C5 H8 O), n-hexyl formate (C7 H14 O2 ), cyclopentane propanoic acid (C8 H14 O2 ), and 2-ethylbutyl acrylate (C9 H16 O2 ). Based on morphological changes and end products formation upon degradation of n -hexadecane implies that the P . aeruginosa PU1 is a effective and robust model in degradation of n -hexadecane and strain can be utilized for reclamation of sites polluted with petroleum sources. Highlights: n -hexadecane degradation by P. aeruginosa PU1 was monitored in BH broth. The uptake of n -hexadecane by P. aeruginosa PU1 was observed by SEM and TEM. The amount of alkane hydroxylase and alcohol dehydrogenase enzymes were evaluated. The impact of biosurfactants on cell surface hydrophobicity was analyzed. Biodegradation of n -hexadecane was confirmed by DCPIP, Gravimetric, FT-IR, and GC-MS analysis.